AN ECONOMIC STUDY ON PRODUCTION AND CHANNELS DISTRIBUTION OF MULTIPLIER ONION IN TIRUNELVELI DISTRICT - Subha, P .Anici; Ebenezer, E. Walsa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Onion is an important vegetable crop and it has gender economic importance among the vegetables since it is one of the leading commodities in agricultural exports. Hence, the economic performance of the crop is of critical importance in improving the efficient use of resources. The cost of production and the net returns obtained per unit would determine the profitability of the crop. The profitability of an enterprise depends upon the efficient use of the resources in production. Further the study of cost of returns structure of onion would help the farmers in ensuring proper resources combinations to augment the onion yield, thereby increasing the profit.